Quality lesson plans for outdoor education - Redmond, Kevin, ....-; Foran, Andrew, ....-; Dwyer, Sean, 1972- (Champaign, IL : Human Kinetics, 2010)
Outdoor activity and adventure is a growing field, but unfortunately, many teachers and recreation leaders and outdoor instructors find themselves without adequate resources to plan and deliver an effective outdoor program. Quality Lesson Plans for Outdoor Education is a flexible, easy-to-use reference that helps physical educators, youth and outdoor recreation leaders, and camp and resort leaders deliver effective outdoor activities. This resource presents the following features: • 21 units with 140 sound lesson plans that are field tested and flexible—meaning they can be adapted for any leader's use • Quick and easy yet thorough and systematic planning and delivery of outdoor topics • CD-ROM with printable lesson plans, worksheets, assessment tools, and more to help leaders deliver a complete, individualized program Quality Lesson Plans for Outdoor Education is useful for experienced professionals and veteran practitioners. Outdoor leaders will discover an abundance of ideas that can make their jobs easier, enrich their teaching knowledge, and broaden their current programs. The CD-ROM allows users to search for and print only the lessons they plan to use. The book provides additional information for teaching in the outdoors, the core skills needed for successful experiences, and 21 activity units composed of 140 lessons. Each chapter presents the purpose of the lessons, the learning outcomes, equipment required, operating principles, skill sets, and risk management. This overview is followed by a series of detailed lesson plans. The resource contains everything needed for delivering each activity. Quality Lesson Plans for Outdoor Education is a great resource for teachers and outdoor leaders, grounding them in the essentials of outdoor education, streamlining their preparation, and paving the the way for a smooth delivery of effective outdoor education.
The CD-ROM allows users to search for and print only the lessons they plan to use. The CD-ROM contains all the units featured in the book in addition to 8 units that are not included in the book.
Includes bibliographical references.
Keywords: Buitensporten; Didactiek; Experiential learning -- Study and teaching -- Handbooks, manuals, etc; Outdoor education -- Study and teaching -- Handbooks, manuals, etc; Outdoor recreation -- Study and teaching -- Handbooks, manuals, etc; Recreation leaders -- Training of -- Handbooks, manuals, etc